2014
DOI: 10.1155/2014/694591
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Survival and Age-Related Outcome in Postsurgery Breast Cancer Patients in a New York City Community Hospital

Abstract: Breast cancer survival has significantly improved over the past two decades. However, the diagnosis of breast cancer is lower and the mortality rate remains higher, in African American women (AA) compared to Caucasian-American women. The purpose of this investigation is to analyze postoperative events that may affect breast cancer survival. This is a retrospective analysis of prospectively collected data from The Brooklyn Hospital Center cancer registry from 1997 to 2010. Of the 1538 patients in the registry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Some of the factors that can influence disease progression include: early diagnosis, staging, histological and biological tumor characteristics, age, ethnic and social factors, and more. [6][7][8] Early diagnosis associated with treatment could reduce the mortality of the disease. [8][9][10][11][12] Disease-free survival (DFS) is defined as the time between the beginning of the treatment and disease progression or death from any cause.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the factors that can influence disease progression include: early diagnosis, staging, histological and biological tumor characteristics, age, ethnic and social factors, and more. [6][7][8] Early diagnosis associated with treatment could reduce the mortality of the disease. [8][9][10][11][12] Disease-free survival (DFS) is defined as the time between the beginning of the treatment and disease progression or death from any cause.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Early diagnosis associated with treatment could reduce the mortality of the disease. [8][9][10][11][12] Disease-free survival (DFS) is defined as the time between the beginning of the treatment and disease progression or death from any cause. [13][14][15] Factors related to a shorter DFS include tumors larger than 2 cm, the presence of lymph node involvement and more advanced stages of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies focusing on NYC have shown disparities by co-morbidities (Van Wye et al 2008), screening rates (Richards et al 2011), and treatment outcomes (Martindale et al 2014). These NYC studies, including studies of other US locations that focus on cancer mortality (Whitman et al 2011; Hirschman, Whitman, and Ansell 2007), have focused on disparities according to racial/ethnic differences.…”
Section: Introductionmentioning
confidence: 99%
“…Martindale et al (2014),Maskarinec et al (2003),Meng et al (1997b),Ning et al (2015),Niu et al (2013),Nurgalieva et al (2013c),Nurgalieva et al (2013a),Ohri et al (2016), O'Malley et al (2003,Owusu et al (2007),Parise and Caggiano (2015),Perkins et al (1996),Potosky et al (1997),Rizzo et al (2015),Roohan et al (1998),Roseland et al (2015),Rueth et al (2014),Rugo et al (2013),Schlichting et al (2012),Shavers et al (2003),Shi et al (2013),Shi et al (2015),Sineshaw et al (2015),,Smith-Gagen et al (2013),Swede et al (2011),Tannenbaum et al (2013),Tao et al (2015),Tichy et al (2015),Wang et al (2015),Wolfson et al (2015),Woodward et al (2006),Wray et al (2013),Wright et al (2012),Yang et al (2009),Yi et al (2012),Schinkel et al (2014),Zeng et al (2015),Zhang et al (2015) Logistic regressionAkinyemiju et al (2015),Akinyemiju et al (2016),Berz et al (2009),Bleicher et al (2016),Boone et al (2014a),…”
mentioning
confidence: 99%